AVARIATIONS IN THE PATTERN OF DISTRIBUTION OF SURAL NERVE ON THE DORSUM OF FOOT - MAMATHA HOSAPATNA,; VRINDA HARI ANKOLEKAR,; ANNE DSOUZA,; ANTONY SYLVAN DSOUZA, (International Journal of Pharma and Bio Sciences, 2016)
Sural nerve supplies skin on the lower lateral part of the back of the leg, the lateral margin and adjoining part of dorsum of the foot and the lateral side of the little toe. The sural nerve is the branch of tibial nerve and it arises in the middle of the popliteal fossa. The present study aims to determine the pattern of the cutaneous distributions of sural nerve of the dorsum of the foot. Sural nerve was dissected in lower limbs of 30 embalmed adult cadavers. The variations in the pattern of innervation were also observed. The SN traced, was highlighted for better visualization and was photographed. Results out of 30 lower limbs, the SN supplied the skin of the foot along its lateral border in 27 cases. A communication between the SN and the lateral branch of superficial peroneal nerve was observed in one case. Three patterns of distribution of SN were observed. Awareness of such anatomical variations is important to surgeons undertaking nerve grafting and other reconstructive procedures.